Redesign of The Presidential Threshold System Following The Constitutional Court Decision Number 62/PUU-XXII/2024 - Arifudin, Arifudin; Susi Dian Rahayu (Universitas Negeri Semarang, 2025)
Since the 2004 elections, Indonesia has implemented a presidential threshold system for nominating the president and vice president. This system requires a political party or coalition to receive a certain percentage of nationally valid votes or acquire a certain number of seats in the DPR in order to nominate a presidential candidate. However, this system's implementation is considered one of the causes of the strengthening of oligarchic practices among political party elites, as well as a deviation from the democratic values of the Indonesian state philosophy, or Pancasila. In January 2025, however, the Constitutional Court canceled the presidential threshold policy for the nomination of the president and vice president through Decision Number 62/PUU-XXII/2024. This research discusses the redesign of the presidential threshold following this decision. The study employs a qualitative approach and draws on Pippa Norris's theory of political recruitment and Wriggs's concept of legal prismatics. This study concludes that the presidential threshold system requires conceptual reform so that it is guided not only by the quantity of valid votes or seats acquired by political parties, but also by considerations of the quality of democracy in presidential and vice presidential elections based on the principles of the Indonesian state philosophy, or pancasila. Thus, the presidential threshold system must be reformed using the concept of legal prismatics.